2012
DOI: 10.2105/ajph.2011.300614
|View full text |Cite
|
Sign up to set email alerts
|

Newly Identified HIV Infections in Correctional Facilities, United States, 2007

Abstract: We used Centers for Disease Control and Prevention HIV Counseling and Testing System data from 2007 to determine the percentage and characteristics of persons newly identified as HIV-positive in US correctional facilities. The newly identified HIV positivity was 0.7%, and 30% of detainees newly identified with HIV were categorized as having low-risk heterosexual contact or no acknowledged risk. Correctional facilities should provide detainees with routine opt-out HIV testing, unless the prevalence of previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…The percentage of new positives also was highest among blacks at 0.5%, although lower than the 1.0% found in a previous study on CDC-funded testing in correctional facilities. 4 These findings are consistent with blacks being disproportionately affected by HIV in the United States. 9,10 …”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The percentage of new positives also was highest among blacks at 0.5%, although lower than the 1.0% found in a previous study on CDC-funded testing in correctional facilities. 4 These findings are consistent with blacks being disproportionately affected by HIV in the United States. 9,10 …”
Section: Discussionsupporting
confidence: 60%
“…For example, a previous study on CDC-funded testing in 2006 found 0.7% new positives. 4 In addition, in comparison to several other CDC-funded site types in 2013, correctional facilities identified a lower percentage of new positives. 24 …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Each year, an estimated 14 % of persons with HIV in the United States enter the correctional system [9]. HIV testing on entry results in diagnosing persons with HIV who were not diagnosed by community HIV testing services [10][11][12][13][14][15], and at year-end 2010, 1.5 % of males and 1.9 % of females entering state and federal prisons were reported to be infected with HIV [16]. Medical services in correctional facilities can improve the health status of incarcerated people with HIV by providing treatment for HIV infection [17][18][19], thereby contributing to the prevention of new HIV infections from incarcerated and released persons with HIV.…”
Section: Introductionmentioning
confidence: 99%